The Entrepreneurial Culture at The Faculty of Administrative Sciences of The UNMSM - Pérez Palácios, Enma Emília (2018)
The present study describes the perception of the entrepreneurial culture in the Faculty of Administrative Sciences (FCA) of the National University of San Marcos (UNMSM), the study population were students and teachers of the faculty, who were surveyed During the academic semester 2016 II. Based on the research findings, reflections are proposed that promote entrepreneurship competencies of interest for management and government in universities. The research problems were: Is there an entrepreneurial culture in the Faculty of Administrative Sciences (FCA) of the UNMSM? And Is this entrepreneurial culture strengthened by activities and organizational climate that motivates the development of entrepreneurship? One of the main results obtained was that students perceive that there is “regular promotion” of the entrepreneurial culture with 53%; while in teachers “little development” by 50%. For this reason, both groups consider that the FCA “should intensify the promotion of the entrepreneurial culture”, in students with 92% and teachers with 87%.